Grenzen einer privaten Super-Liga im europäischen Spitzenfußball Eine unionskartellrechtliche Analyse - Haug, Niko (Schriften zum Sportrecht, 2023)
The object of this publication is to explore the legal limits of a European Super League. Like the ECJ in Case C-333/21, the author examines the question of whether UEFA may regulate breakaway competitions and sanction clubs and players for participating in such competitions in order to protect the established structures of the European sports model. Unlike the ECJ, he also analyses the compatibility of UEFA's new authorisation rules governing international club competitions (edition 2022) with EU antitrust law. Furthermore, the subject of the work is the admissibility of a closed European Super League under EU antitrust law.